PERAN KOMUNITAS BASIS GEREJAWI BAGI EFEKTIVITAS PELAKSANAAN KARYA PASTORAL PARTISIPATIF DAN KONTEKSTUAL - Jewadut, Jean Loustar; Nirmala, Fransiska Rosari (Lembaga Penelitian STKIP Widya Yuwana, 2023)
The development of the Church as an organism demands active participation and cooperation between clergy and laity. The purpose of this article is to introduce Basic Ecclesiastical Community (KBG) as a model of church life which is a place for the involvement of the laity in collaboration with the clergy. This article was written using qualitative research methods with a focus on literature studies in the form of books and scientific journal articles according to the themes reviewed. The results of the literature study in this article confirm several important things. First, the model of church life through KBG empowerment can minimize the tendency of clerical feudalism. Pastoral officers (clergy) must act as facilitators, not rulers who authoritatively regulate church life. Second, KBG makes the implementation of participatory and contextual pastoral works effective. Participatory pastoral work means involving as many people as possible in planning, implementing, and evaluating pastoral activities, while contextual pastoral work means pastoral work that departs from a particular context and must respond to the context. Third, the spirit of a shepherd's life smelling of sheep plays an important role for the realization of participatory and contextual pastoral work.